New perspectives on mobile phone addiction based on network analysis - Qiu, Rui; Guo, Zhihua; Wang, Xianyang; Li, Yushan; Li, Mengze; Xia, Zhu (Frontiers in Psychiatry, 2025)
BackgroundMobile phone addiction represents a widespread concern associated with negative health consequences, influenced by various protective and risk factors. Nonetheless, two significant gaps persist in the literature: the examination of gender differences in the interplay among mobile phone addiction symptoms, and the analysis of dimension-level associations between mobile phone addiction and its determinants. These gaps motivated the current investigation. This study aimed to elucidate the interconnections among symptoms of mobile phone addiction through the development of a relational network and the identification of key central symptoms. Furthermore, it investigated the influence of fundamental psychosocial factors on mobile phone addiction, with a specific focus on gender-related differences.MethodsThe sample comprised 1,684 adults. Participants completed validated self-report instruments, including the Mobile Phone Addiction Tendency Scale (MPATS) and the Connor-Davidson Resilience Scale (CD-RISC), to assess mobile phone addiction and relevant psychosocial factors. Network analysis techniques were employed to construct two models: a standalone symptom network of mobile phone addiction and an integrated network incorporating addiction symptoms and influencing psychosocial factors. Additionally, gender-stratified analyses were conducted to compare network structures and centrality metrics between male and female groups.ResultsAcross both genders, the most robust associations within the mobile phone addiction symptom network were confined to items within the same MPATS dimension. The strongest edge common to both networks connected Item 4 (“I would feel bad if I did not use my phone for a long time”) and Item 6 (“I would feel lonely without my mobile phone”), both reflecting withdrawal symptoms. The second strongest association linked Item 7 (“I feel more confident when I communicate with others using my phone”) and Item 16 (“I feel more comfortable when I communicate with others via cell phone”), which pertain to the social comfort dimension. Regarding central symptoms, Item 15 (“In class/at work, I often take the initiative to focus on my mobile phone, which affects the lesson/work”) emerged as the central node among males, whereas Item 6 (“I would feel lonely without my mobile phone”) was central among females. Within the integrated network, the strength dimension of psychological resilience served as the central node for both genders. Additionally, in the male sample, the positive reappraisal dimension of cognitive emotion regulation strategies was identified as the central node, whereas the catastrophizing dimension emerged as the central node in the female sample.ConclusionThe results demonstrate significant gender disparities within both the isolated mobile phone addiction symptom network and the comprehensive network that includes psychosocial variables. Strong connections were observed particularly within the withdrawal and social comfort domains, accompanied by gender-specific central symptoms—namely, task-interfering phone use among males and feelings of loneliness among females. These findings contribute to a deeper comprehension of the psychopathological processes associated with mobile phone addiction. Moreover, they identify specific focal points for the formulation of gender-responsive intervention strategies designed to reduce mobile phone addiction.